Namierzanie inwestorów jako metoda pozyskiwania bezpośrednich inwestycji zagranicznych - Kuźmińska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The importance of foreign direct investment (FDI) for economic development increases attention for attraction of FDI. Most countries have established investment promotion programmes which are conducted by investment promotion agencies (IPA). The core IPA functions are image building, investor targeting and also pre-investment and after-care services. Investor targeting has become a very important activity among active and effective agencies. It involves the focusing on attracting specific companies that have a genuine intention, resources and capabilities to invest in a country. Most of the effective IPAs target industries, types of company and specific corporations. The Polish Information and Foreign Investment Agency doesn't use investor targeting to attract FDI but is planning to do so in the future. Investor targeting is becoming more and more important but it will not be effective if the country cannot offer good conditions to do a business. All promotion activities need to go hand in hand with investment friendly policy and appropriate economic conditions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 196-203